The Effect of Implementing Interactive Video-Based E-Learning on Motivation to Learn the Arba'in Nabawi Hadith - Muhammad, Devy Habibi; Turrohmah, Bail Miya; Pramudita, Audi; Wardhani, Maharani Kusuma; Aisyah, Siti; Alatise, Toyosi; Alsokari, Tareq (JERIT: Journal of Educational Research and Innovation Technology, 2025)
The use of digital media, such as educational games in digital format, not only increases learning motivation, but can also help introduce technology to students from an early age, so that they become familiar and proficient in using it. In addition, digital skills are also important to prepare a generation that is able to compete in the technological era. This study aims to analyze the effect of implementing interactive video-based e-learning on students' learning motivation in the subject of Hadith Arba'in Nawawi at SMP IT Al-Amri. The background of this study is based on the low learning motivation of students due to the dominance of conventional learning methods with minimal interaction and the suboptimal use of digital media by educators. This study uses a quantitative approach with an experimental design, involving 30 students as a sample. The research instrument in the form of a questionnaire was validated through validity and reliability tests, with a Cronbach's Alpha result of 0.905 indicating high consistency. Data analysis was carried out using simple linear regression through the SPSS version 31 application. The results showed that interactive video-based e-learning had a significant effect on students' learning motivation with a coefficient of determination (R²) of 0.236. This means that 23.6% of the variation in students' learning motivation can be explained by the use of interactive video media, while the rest is influenced by other factors. These findings indicate the importance of digital innovation in religious learning to increase student engagement and interest in learning, especially in the context of Islamic education. This study recommends that teachers be more active in developing digital learning media that are contextual, interesting, and in accordance with the characteristics of digital generation students.